Preserving Honor from the Influence of Negative Modern Lifestyles: A Maqāṣidī Exegetical Analysis of QS. An-Nur Verses 30–32 - Eka Dwi Jayanti; Eka Prasetiawati; Wahyudi Wahyudi (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2026)
Amid the expanding waves of digital transformation, human moral integrity is facing new challenges in the form of visual exposure and the commodification of the body in cyberspace. This article aims to actualize the essential message of QS. An-Nūr verses 30–32 through the perspective of Tafsīr Maqāṣidī as formulated by Abdul Mustaqim, in order to address the challenges posed by increasingly open modern lifestyles. Employing a qualitative method based on library research, and utilizing a maqāṣidī exegetical approach to QS. An-Nūr verses 30–32, this study seeks to uncover the Islamic concept of honor, which is then contextualized within contemporary social realities to produce findings that are systematic, analytical, and scientifically accountable. The findings indicate that the verses on honor are not merely strict regulations, but rather constitute a comprehensive system for the protection of human dignity, particularly through the commands to lower the gaze and cover the ‘awrah as stated in QS. An-Nūr verses 30–31. This meaning becomes increasingly relevant in the context of digital engagement and the exercise of privacy control to prevent the negative impacts of social media practices. Furthermore, the recommendation of marriage in verse 32 is positioned as a primary solution, while also addressing economic barriers arising from consumptive lifestyle standards. In synthesis, Islamic law provides a holistic framework of protection encompassing mindset, social ethics, and practical solutions in safeguarding human honor and dignity. Through this perspective, the Qur’an functions as a robust moral shield for individuals in preserving spiritual values amid the currents of globalization.